Foreign market entry process of AROS-osiva company - Engelová, Natalie; Černá, Iveta, 1979-; Křenková, Eva; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis explores the potential international expansion of the Czech agricultural company AROS-osiva s.r.o., which specializes in the production and sale of grass seeds and seed mixtures. The aim is to identify the most suitable foreign market and entry strategy based on internal capabilities and external market conditions. The theoretical part introduces key concepts such as motives for internationalization, entry modes, and strategic analytical tools including PESTLE, SWOT, VRIO, and Porter’s Five Forces. The practical part applies these frameworks to analyze AROS-osiva and evaluates Austria as the most favorable target market. Through a combination of qualitative and quantitative methods, including a scoring model and a managerial interview, the study concludes that direct export with local distribution partners presents the most effective and low-risk approach for entering the Austrian market.
Vedoucí práce: Iveta Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses